Soluble C-Type Lectin-Receptor Ligands Stimulate ROS Production in Dendritic Cells and Potentiate Killing of MRSA as Well as the MRSA Induced IL-12 Production - Eld, Helene M. S.; Johnsen, Peter R.; Nielsen, Emilie M.; Jørgensen, Frederikke Z.; Lindstrøm-Svendsen, Marie; Baldry, Mara; Ingmer, Hanne; Frøkiær, Hanne (Frontiers in Immunology, 2022)
Methicillin resistant Staphylococcus aureus (MRSA) has developed resistance to most β-lactam antibiotics leaving few treatment options against infections with MRSA. Through mannose receptors, mannan potentiates IL-12 production induced by Gram-positive bacteria, a cytokine crucial in the clearance of S. aureus infection. We investigated the IL-12 potentiating effect of mannan pre-treatment of bone marrow-derived dendritic cells prior to stimulation with clinical MRSA strains. Mannan almost doubled IL-12 as well as IFN-β production in response to USA300, also when USA300 was treated with the β-lactam cefoxitin. The MRSA-induced IL-12 production was dependent on bacterial uptake and reactive oxygen species (ROS). Mannan alone induced ROS production, and in combination with USA300, the ROS produced corresponded to the sum induced by mannan and USA300. Addition of a monoclonal antibody against the mannose receptor likewise enhanced USA300-induced IL-12 and induced ROS production. Mannan addition further increased the endocytosis as well as the rate of endosomal killing of bacteria. Pre-treatment with soluble β-glucans also induced ROS and potentiated the USA300-induced IL-12 indicating that other C-type receptors may play a similar role. In the presence of the pro-inflammatory mediators, GM-CSF or IFN-γ, the mannan-enhanced IL-12 production increased further. The USA300-induced and the mannan-facilitated enhanced IFN-β and IL-12 showed same dependency on MAPK c-Jun N-terminal kinase signaling, suggesting that mannan enhances the signals already induced by the bacteria, rather than changing them. We suggest that the C-type lectin-induced ROS production is a key factor in the IFN-β and IL-12 potentiation.